2012
DOI: 10.1142/s0219749912500487
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Information Approach to Normal Representation of Extensive Games

Abstract: We modify the concept of quantum strategic game to make it useful for extensive form games. We prove that our modi¯cation allows us to consider the normal representation of any¯nite extensive game using the fundamental concepts of quantum information. The Selten's Horse game and the general form of two-stage extensive game with perfect information are studied to illustrate a potential application of our idea. In both examples we use the EisertÀ WilkensÀLewenstein approach as well as the MarinattoÀWeber approac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
23
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 14 publications
0
23
0
Order By: Relevance
“…However, the previous results do not explain (even in a simple two-stage quantum game) how to identify behavioral strategies, information sets and other terms connected with extensive game theory. In our recent papers [3,4] we have proposed a way of quantizing extensive games without chance moves through their normal representation which covers not only two-stage extensive games but also more complex games, including games with imperfect information. In this paper, with the use of a signaling game, we generalize our idea by allowing a chance mover to perform a quantum operation.…”
Section: Introductionmentioning
confidence: 99%
“…However, the previous results do not explain (even in a simple two-stage quantum game) how to identify behavioral strategies, information sets and other terms connected with extensive game theory. In our recent papers [3,4] we have proposed a way of quantizing extensive games without chance moves through their normal representation which covers not only two-stage extensive games but also more complex games, including games with imperfect information. In this paper, with the use of a signaling game, we generalize our idea by allowing a chance mover to perform a quantum operation.…”
Section: Introductionmentioning
confidence: 99%
“…Though it was created for research on Nash equilibria in quantum 2 × 2 games, it has also found application in studying some of the refinements of a Nash equilibrium like evolutionarily stable strategies [2]. Moreover, it has been proved that the MW scheme is applicable to finite extensive games [3] and even various problems of duopoly [4,5,6]. These recent papers show uninterrupted interest in research on quantum games played according to the MW idea and they provide sufficient motivation to improve the existing results.…”
Section: Introductionmentioning
confidence: 99%
“…Though it was created for research on Nash equilibria in quantum 2 × 2 games, it has also found an application in studying some of the refinements of a Nash equilibrium, such as evolutionarily stable strategies [2,3]. Moreover, the MW scheme turns out to be applicable to finite extensive games [4]. Among other applications, the problem of duopoly is worthy noting.…”
Section: Introductionmentioning
confidence: 99%